(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article explores the symbiotic relationship between food and nutritional science and commerce, highlighting the critical intersections that drive sustainable health and economic prosperity. By examining the dynamic interplay between these fields, we delve into the evolving landscape of nutrient economics, where investments in food innovation, supply chain management, and consumer behavior contribute not only to individual well-being but also to the economic vitality of communities.